Օտարման և փախուստի խնդիրը արդի հայ արձակում - Ոսկանյան, Ռուզաննա (ՀՀ ԳԱԱ Գրականության ինստիտուտ)
В данной статье рассматриваются две концепции, которые занимают центральное место в философии экзистенциализма: отчуждение и побег. Предметом исследования является современная армянская проза, в частности литература Гургена Ханджяна, Левона Хечояна, Ваагна Григоряна, Рафаэля Нахапетяна, Грачья Сарибекяна, Оганеса Текгёзяна и Арама Пачяна. Цель статьи показать, что отражение проблемы побега и отчуждение в армянской литературе - это не прямое влияние философии бытия, а результат исторических и психологических обстоятельств. In this article, two concepts are considered that occupy a central place in the philosophy of existentialism: alienation and escape. The subject of the study is modern Armenian prose, in particular the literature of Gurgen Khanjyan, Levon Khechoyan, Vahagn Grigoryan, Rafael Nahapetyan, Hrachya Saribekyan, Hovhannes Tekgyozyan and Aram Pachyan. The purpose of the article is to show that the reflection of the problem of escape and alienation in Armenian literature is not a direct influence of the philosophy of being, but the result of historical and psychological circumstances.
Keywords: Գրականություն